Factors in Building Employee Commitment: Mediating Role of Job Satisfaction at Bank Central Asia - Andoko Chandra; Andreas Saputra; Anto Broto; Dorotea Pamungkas; Khomensyah Nasution (IJHCM (International Journal of Human Capital Management), 2021)
This study aims to establish an understanding of specific factors in HR practices in BCA upon employee commitment and the role of job satisfaction as a mediating role. The study analyzed four factors with a sample of 409 employees in Bank Central Asia, Tbk. The researchers used regression analysis to investigate the hypothesis. The findings revealed that job enrichment and job training in Bank Central Asia were positively related to job satisfaction and employee commitment. Salary and job stability were found to be insignificant factors in job satisfaction. Job satisfaction mediates the effect of salary, job enrichment, and job training but not job stability. We hope to provide insight into the role of HR best practices in Bank Central Asia, Tbk, as one of the top-performing banks in Indonesia.